Transthoracic Lung Ultrasound in Systemic Sclerosis-Associated Interstitial Lung Disease: Capacity to Differentiate Chest Computed-Tomographic Characteristic Patterns - Cinzia Rotondo; Giuseppe Busto; Valeria Rella; Raffaele Barile; Fabio Cacciapaglia; Marco Fornaro; Florenzo Iannone; Donato Lacedonia; Carla Maria Irene Quarato; Antonello Trotta; Francesco Paolo Cantatore; Addolorata Corrado (Diagnostics)
Background/Objectives: Even today, interstitial lung disease (ILD) is diagnosed by chest high-resolution computed tomography (lung HR-CT). Large amounts of data are available about the usefulness of transthoracic lung ultrasound (LUS) in ILD. This study aimed to evaluate the transthoracic LUS capacity to discriminate different ILD patterns in systemic sclerosis (SSc) patients, such as usual interstitial pneumonia (UIP), non-specific interstitial pneumonia (NSIP) with ground glass opacification/opacity (GGO), and NSIP with GGO and reticulations, as well as the possibility of identifying progressive fibrosing ILD. Methods: We enrolled SSc-patients attending the outpatient Clinic of the Rheumatology Unit of Policlinico of Foggia and the Rheumatology Unit of Policlinico of Bari who satisfied these inclusion criteria: age older than 18 years; the satisfaction of ACR/EULAR 2013 classification criteria for SSc; chest HR-CT scan within three months before or three months after transthoracic LUS evaluation; and availability of recent and complete pulmonary function test. The exclusion criteria were as follows: history or recent reactivation of chronic obstructive pulmonary disease, lung cancer, lung infection, heart failure, pulmonary oedema, pulmonary arterial hypertension, acute respiratory distress syndrome and diffuse alveolar haemorrhage and thoracic surgery. All enrolled SSc-patients underwent transthoracic LUS, performed by an experienced sonographer. The ILD diagnosis and the respective patterns were assessed by chest HR-CT, which still represents the best diagnostic tool. Results: ILD was observed in 99 (63.5%) patients. Of these, 25% had the UIP pattern and 75% the NSIP pattern (46 with GGO, 28 with GGO and reticulations). By receiver operating characteristic (ROC) curve analysis, higher values of accuracy, sensitivity, specificity, and negative clinical utility index (CUI) were found for pleural line irregularity (0.84 (95% CI: 0.75–0.91), 96%, and 73.6%, p = 0.0001; 0.72), and pleural line thickness (0.84 (95% CI: 0.74–0.91), 72%, and 96.4%, p = 0.0001; 0.85) for detecting the UIP pattern. The best performance among transthoracic LUS signs for NSIP with the GGO pattern was observed for B-lines (accuracy: 0.88 (95% CI: 0.80–0.93), sensitivity: 93.4% and specificity: 82.4, p = 0.0001; CUI+: 0.75, CUI−: 0.77). LUS signs with higher accuracy, sensitivity, and specificity for NSIP with GGO and reticulations were pleural line irregularity (0.89 (95% CI: 0.80–0.95), 96.4%, and 82.4%, p = 0.0001) with CUI−: 0.72, and B-lines (0.89 (95% CI: 0.80–0.95), 96.4%, 82.4%, p = 0.0001), with CUI+: 0.80 and CUI−: 0.70. Furthermore, a total number of B-lines > 10 maximises LUS performance with 92.3% sensitivity, and an accuracy of 0.83 (p = 0.0001) for detecting the NSIP pattern, particularly GGO. A sample-restricted analysis (66 SSc patients) evidenced the presence of progressive fibrosing ILD in 77% of these patients. By binary regression analysis, the unique LUS sign associated with progressive fibrosing ILD was the presence of pleural line irregularity (OR: 3.6; 95% CI 1.08–11.9; p = 0.036). Conclusions: Our study demonstrated that transthoracic LUS presented a high capacity to discriminate the different patterns of SSc-ILD. Therefore, the hypothesis that transthoracic LUS is an effective screening method for the evaluation of the presence of SSc-ILD and establishing the correct timing of chest HR-CT, in order to avoid patients receiving excessive exposure to ionising radiation, is supported.